A novel method to prepare columnar grains of TiAl alloys by controlling induction heating. (November 2019) - Liu, Yangli; Xue, Xiang; Chen, Ruirun; Tan, Yingmei; Su, Yanqing; Ding, Hongsheng; Guo, Jingjie
Abstract: In order to obtain columnar grains of TiAl alloys by heat treatment instead of directional solidification, a new method named as directional induction heat treatment (DHT) has been put forward. Numerical simulation of temperature field and experiments for DHT has been carried out. Temperature fields of TiAl ingots with different diameters under different loaded power have been calculated. The results show that temperature difference between the surface and axis of TiAl ingots increases with the increasing of diameter from 20 mm to 50 mm or power from 10 kW to 30 kW, under skin effect and heat conduction inner. But there is almost no temperature difference in the ingot with diameter of 20 mm, no matter how high the power is. Based on above calculated results, an ingot with diameter of 20 mm was pushed upwards at intervals of 15 mm and was induction heated under different loaded power correspondingly. The temperature of DHT area could be controlled by adjusting loaded power. In the range of 1732 K–1773 K, β phase transformation will occur and β grains grow up continuously with the pulling of the Ti44Al ingot. In this way, columnar grains of Ti44Al alloy have been obtained.